Application of the spectral method to stochastic filter analysis - Kharchenko, O.I. (Вопросы атомной науки и техники, 2019)
The problem of standing out a signal from an additive mixture of a harmonic signal and white Gaussian noise is considered. The analysis is based on the phenomenon of stochastic resonance (SR), which consists in amplifying a periodic signal under the influence of noise of a certain power. SR is a universal physical phenomenon that is typical of some nonlinear systems, and is came out not only in technical, but also in biological and social systems. When calculating the spectral characteristics of the output signal, Volterra series were used. The problem is solved using the transfer functions of Volterra without the initial definition of kernels. Volterra transfer functions are obtained by the harmonic input signal method. The influence of the input signal parameters, in particular the amplitude and frequency of the harmonic signal and the noise power, on the spectral power density of the output signal is studied. Optimal parameters values are determined. Criteria are formulated for using a stochastic filter to standing out a harmonic signal on the background white Gaussian noise. Розглянуто задачу виділення сигналу з адитивної суміші гармонійного сигналу і білого гаусова шуму. В основу аналізу покладено явище стохастичного резонансу (СР), яке полягає в посиленні періодичного сигналу під дією шуму певної потужності. СР є універсальним фізичним явищем, яке типове для деяких нелінійних систем, і проявляється не тільки в технічних, але і в біологічних, і соціальних системах. При розрахунку спектральних характеристик вихідного сигналу використовувалися ряди Вольтерра. Задача розв’язана допомогою передавальних функцій Вольтерра без початкового визначення ядер. Передавальні функції Вольтерра отримані методом гармонійного вхідного сигналу. Досліджено вплив параметрів вхідного сигналу, зокрема амплітуди і частоти гармонійного сигналу і потужності шуму, на спектральну щільність потужності вихідного сигналу. Визначено значення оптимальних параметрів. Сформульовано критерії застосування стохастичного фільтра для виділення гармонійного сигналу на тлі білого гаусова шуму. Рассмотрена задача выделения сигнала из аддитивной смеси гармонического сигнала и белого гауссова шума. В основу анализа положено явление стохастического резонанса (СР), которое заключается в усилении периодического сигнала под действием шума определенной мощности. СР является универсальным физическим явлением, которое типично для некоторых нелинейных систем, и проявляется не только в технических, но и в биологических и социальных системах. При расчете спектральных характеристик выходного сигнала использовались ряды Вольтерра. Задача решена с помощью передаточных функций Вольтерра без первоначального определения ядер. Передаточные функции Вольтерра получены методом гармонического входного сигнала. Исследовано влияние параметров входного сигнала, в частности амплитуды и частоты гармонического сигнала и мощности шума, на спектральную плотность мощности выходного сигнала. Определены значения оптимальных параметров. Сформулированы критерии применения стохастического фильтра для выделения гармонического сигнала на фоне белого гауссова шума.